Everyday Las Vegas : Local Life in a Tourist Town - Rowley, Rex J., 1977- (Book collections on Project MUSE., 2013)
Every year, more than thirty-five million people from all over the world visit Las Vegas; only two million call the city home. This book takes a close look at the lives of those who live in a place the rest of the world considers exotic, even decadent.